The impact of shared leadership on teamwork mental models and performance in self-directed teams. (January 2013) - McIntyre, Heather H.; Foti, Roseanne J.
The purpose of this study was to clarify the role of shared leadership in self-directed teams by testing its relationship with teamwork mental models and team performance. Data from 40 intact, naturally occurring teams involved in highly interdependent tasks demonstrated that the distribution of informal leadership and whether or not perceptions of leadership were reciprocated among leaders were related to the degree of similarity and accuracy of team mental models as well as subsequent team performance. Specifically, teams with a coordinated type of shared-leadership perception demonstrated significantly higher levels of team mental model similarity, team mental model accuracy, and team performance than teams with a distribution of leaders that failed to recognize each other as leaders as well as teams with no leaders. However, teams with distributed-coordinated leadership were significantly different than teams with centralized leadership only with respect to team mental model accuracy scores. Finally, this study builds on prior research by demonstrating that the team mental model accuracy contributes more to team performance than team mental model similarity.